Molecular and functional characterization of the extracellular calcium-sensing receptor in human colon cancer cells. - Kállay, E; Bonner, E; Wrba, F; Thakker, R; Peterlik, M; Cross, H (2003)
Presence of a functional extracellular calcium-sensing receptor (CaR) is of particular relevance for the growth-inhibitory action of Ca2+ on human colon carcinoma cells. In order to detect CaR gene alterations that may have occurred during the tumorigenic process, we applied Southern blot, DNA sequence, and RT-PCR analysis to DNA from normal human colon mucosa and from cancerous lesions of different grading, as well as from primary cultured and established colonic carcinoma cell lines (e.g., Caco-2). No evidence was obtained for mutations or other sequence alterations in the CaR gene in any of the colon carcinoma cells analyzed. Only a differential expression of two splice variants of the CaR gene, which are generated by usage of different promoters in the 5'-untranslated region, was detected in colon carcinomas of different grade. From Western blot analysis a tendency towards lower CaR protein levels in carcinoma cells in parallel with tumor progression became apparent. Activation of the CaR by extracellular Ca2+ or by specific receptor agonists resulted in substantial growth inhibition in Caco-2 cells. Activation of the CaR was transduced into inhibition of phospholipase A2-mediated arachidonic acid formation, but also into increased production of cAMP and IP3. This provides evidence for a cell type-specific function of the CaR in human colonocytes. We conclude that neoplastic colon epithelial cells can respond to antimitogenic signals generated by activation of the CaR as long as they express sufficient amounts of the CaR protein. This provides a rationale for the use of calcium in chemoprevention of colon tumor development.